Allylimidazole containing OSTE based photocured materials for selective and efficient removal of gold from aqueous media - ÇAKMAKÇI, EMRAH; AYDIN URUCU, OYA (ELSEVIER SCIENCE BV, 2019)
Off-Stoichiometry Thiol-Ene (OSTE) photopolymerization technique provides an innovative platform for the development of materials with tunable mechanical and surface properties. In this work, this technique was used to prepare polymeric materials that can effectively and selectively adsorb Au(III) from aqueous solutions. The use of OSTE technique brought simplicity and speed. OSTE based photocured discs were prepared from commercial monomers (trimethylolpropane tris(3-mercaptopropionate) and 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione) by UV curing and 1-allyimidazole was also introduced to incorporate imidazole functionality. Then disc shaped photocured resins were used for the recovery studies. The effects of pH, imidazole group, contact time were investigated to determine the optimal conditions. The optimal contact time was found as 5 h while the optimum pH was determined as 1.5. The adsorption profile of the OSTE based discs was well fitted to Langmuir adsorption isotherm model (??R-2: 0.997, chi(2): 1.455). In the presence of different metal cations such as Cu (II), Cd (II) and Pb (II) imidazole containing photocured discs showed high selectivity towards Au (III). It was also found that the photocured resins could be regenerated and reused for successfully for five times. The OSTE based photocured adsorbent resins were also tested to remove Au (III) ions from a gold ore and river water samples and the resin exhibited over 90% Au (III) ions recovery in all samples.
Keywords: Thiol-ene; OSTE; Au(III); Adsorption; Photocuring; Imidazole; ENE CLICK REACTION; COVALENT IMMOBILIZATION; METHYLENE-BLUE; GRAPHENE OXIDE; AU(III) IONS; ADSORPTION; RECOVERY; GOLD(III); NANOCOMPOSITE; LIQUID